2016
DOI: 10.17795/jjnpp-40069
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of an Iranian Traditional Dosage Form Containing Linum and Ficus for Improvement of Functional Constipation

Abstract: Background: Constipation is a common gastrointestinal problem worldwide. Objectives: The current study aimed to prepare a dosage form containing flaxseed and figs and evaluate the effects of this drug to treat functional constipation. Methods: A total of 10 formulations were developed using various proportions of excipients by wet granulation method. The best formulation containing 300 mg flaxseed powder and 1200 mg figs extract (total weight of 2000 mg) was selected. After compression of caplets, evaluation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A randomized doubleblind study showed that F. carica paste may have valuable effects in patients suffering from constipation (30). The severity of FC significantly reduced after consumption of Linum and Ficus (31). Evidence revealed that dysbiosis of gut microbiota might contribute to FC and IBS (32).…”
Section: Discussionmentioning
confidence: 96%
“…A randomized doubleblind study showed that F. carica paste may have valuable effects in patients suffering from constipation (30). The severity of FC significantly reduced after consumption of Linum and Ficus (31). Evidence revealed that dysbiosis of gut microbiota might contribute to FC and IBS (32).…”
Section: Discussionmentioning
confidence: 96%